2019
DOI: 10.3390/genes10100735
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum and Clinical Features of Patients with LOXHD1 Variants Identified in an 8074 Hearing Loss Patient Cohort

Abstract: Variants of the LOXHD1 gene, which are expressed in hair cells of the cochlea and vestibule, have been reported to cause a progressive form of autosomal recessive non-syndromic hereditary hearing loss, DFNB77. In this study, genetic screening was conducted on 8074 Japanese hearing loss patients utilizing massively parallel DNA sequencing to identify individuals with LOXHD1 variants and to assess their phenotypes. A total of 28 affected individuals and 21 LOXHD1 variants were identified, among which 13 were nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…A series of studies have shown that patients with LOXHD1 mutations show progressive hearing loss, leading to profound‐to‐severe non‐syndromic hearing loss (Mori et al, ; Maekawa et al, ). By examining a large cohort of hearing loss patients (n = 8,074), we have recently reported 28 patients with LOXHD1 mutations and clarified the clinical features (Maekawa et al, ). Concerning the audiogram configurations, most of the patients had high‐frequency hearing loss (Fig.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%
See 4 more Smart Citations
“…A series of studies have shown that patients with LOXHD1 mutations show progressive hearing loss, leading to profound‐to‐severe non‐syndromic hearing loss (Mori et al, ; Maekawa et al, ). By examining a large cohort of hearing loss patients (n = 8,074), we have recently reported 28 patients with LOXHD1 mutations and clarified the clinical features (Maekawa et al, ). Concerning the audiogram configurations, most of the patients had high‐frequency hearing loss (Fig.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%
“…All CI patients, whose clinical data were available, showed a favorable outcome (Fig. ) (Maekawa et al, ). Therefore, patients with this gene mutation are good candidates for CI/EAS.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%
See 3 more Smart Citations